Applications of Single-Electron Devices for Nanoscale Quantum Precision Measurement - Wang, Yanbo (Exploring Science Academic Conference Series, 2026)
Single-electron devices with the Coulomb blockade effect and single -electron tunneling effect are able to accurately control the quantum state of an electron. This paper systematically investigates its application in this field as the core carrier to overcome the limitations of traditional measurement technology and realize nanoscale quantum precision measurement. The paper conducts a deep analysis about its technical principle, typical device structure, and performance optimization mechanism. Firstly elaborating the core physics behind single-electron phenomena and key features of devices; secondly taking devices including Single -Electron Transistors (SETs), and single -electron boxes as examples detailing their applications in regulating quantum states, detecting nanoscale magnetic/electric fields, and characterizing single -molecule charges. Emphasize the novel designs and measurement performances of new devices like twisted bilayer graphene quantum dot SETs and room -temperature silicon -based SETs. Las tly discuss existing device -related issues regarding stability, integration, and environmental interference, and look forward to future developments in quantum sensing, quantum computing, and biomedicine. Our research shows that through precise control of quantum effects, single -electron devices enable ultra -high sensitivity measurements of physical quantities at the nanoscale, which is a revolutionary solution for atomic -level detection and brings great scientific value and engineering applications.